Predictors of renal involvement in patients with systemic lupus erythematosus - Satirapoj B. (2014)
From a cohort of 109 patients (105 females and 4 males) treated for systemic lupus erythematosus (SLE), 20 patients (18.3%) developed new episodes of lupus nephritis and 89 patients (81.7%) remained free of renal involvement during the follow-up period. The mean duration of follow up was 39.1 ± 54.4 months. Clinical characteristics associated with developing lupus nephritis were a high systolic blood pressure (≥ 130 mmHg), photosensitivity, cutaneous vasculitis and gastrointestinal (GI) symptoms. Laboratory abnormalities associated with the development of lupus nephritis were hemoglobin < 10 mg/dl, hematocrit < 30%, blood urea nitrogen > 12 mg/dl, serum creatinine > 1.3 mg/dl, ESR > 60, the third component of complement (C3) level < 0.45 and positive anti-dsDNA antibody. After a multivariable analysis, only high systolic blood pressure, cutaneous vasculitis, hemoglobin < 10 mg/dl and serum creatinine > 1.3 mg/dl remained as statistically significant risk factors for developing lupus nephritis.